Green Accounting, Corporate Social Responsibility Disclosure, and Stock Prices in Indonesia’s Energy Sector, 2019–2023: Implications for SDG 12 - Setiadi Setiadi; Muhamad Taqi; Tri Lestari; Agus Sholikhan Yulianto (Journal of Current Studies in SDGs, 2027)
Objective: The study examines the effects of green accounting and corporate social responsibility disclosure on the stock prices of oil, gas, and coal companies listed on the Indonesia Stock Exchange. It also considers the relevance of corporate sustainability disclosure to Sustainable Development Goal 12, particularly the promotion of responsible and transparent business practices. Method: The study employed a quantitative explanatory design using secondary data obtained from annual reports, sustainability reports, PROPER assessments, GRI-based disclosures, and stock-price information. The population consisted of 87 energy-sector companies observed from 2019 to 2023. Purposive sampling generated a final sample of 10 companies and 50 firm-year observations. The data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, partial and simultaneous hypothesis tests, and the coefficient of determination. Results:  Green accounting had a statistically significant partial effect on stock prices, whereas corporate social responsibility disclosure did not demonstrate a significant partial effect. Simultaneously, the two disclosure variables did not significantly explain stock-price variation at the 5% significance level. The adjusted coefficient of determination was 8.0%, indicating that most stock-price movements were explained by factors outside the model. Novelty: The study integrates PROPER-based environmental performance, GRI-oriented CSR disclosure, and capital-market outcomes within Indonesia’s extractive energy sector. It demonstrates that sustainability information alone remains insufficient to explain investor valuation, highlighting the need for more comparable, decision-useful, and credible disclosure practices supporting SDG 12.